100 s negative ion accelerations for the JT-60SA negative-ion-based neutral beam injector. (23rd December 2021) - Kashiwagi, M.; Hiratsuka, J.; Ichikawa, M.; Saquilayan, G. Q.; Kojima, A.; Tobari, H.; Umeda, N.; Watanabe, K.; Yoshida, M.; Grisham, L.
Abstract: In the negative-ion-based neutral beam injector (N-NBI) of JT-60SA, a hydrogen negative ion beam with energy of 500 keV and a current density of 154 A m −2 for 118 s has been successfully demonstrated. This achievement exceeds the requirements (500 keV, 130 A m −2, 100 s) for the first time. To maintain stable negative ion production for a long pulse, the optimal temperatures of the chamber wall and plasma grid were analytically examined and were experimentally demonstrated. It was confirmed that the temperature during the beam pulse should be <50 °C for the chamber wall and >200 °C for the plasma grid. Damage to the filament cathode due to an abnormal discharge, so-called arcing, has been mitigated by developing a fast cut-off system of the arc current for around 100 μ s after the arcing. To maintain sufficient voltage holding capability and to reduce the grid heat load due to the beam in the accelerator, techniques developed for the beam acceleration have been applied to this test. As a result of the integration of these techniques, a stable beam over 100 s has been demonstrated successfully. This is the first achievement over a 100 s stable beam with intensity of >75 MW m −2, which is the required practical level in the N-NBI. These results contribute to the coming NBI system for ITER and DEMO.